Cyanobacteria Inoculation Improves Soil Stability and Fertility on Different Textured Soils: Gaining Insights for Applicability in Soil Restoration - Chamizo, Sonia; Mugnai, Gianmarco; Rossi, Federico; Certini, Giacomo; De Philippis, Roberto (Frontiers in Environmental Science, 2018)
Cyanobacteria are ubiquitous components of biocrust communities and the first colonizers of terrestrial ecosystems. They play multiple roles in the soil by fixing C and N and synthesizing exopolysaccharides, which increase soil fertility and water retention and improve soil structure and stability. Application of cyanobacteria as inoculants to promote biocrust development has been proposed as a novel biotechnological technique for restoring barren degraded areas and combating desertification processes in arid lands. However, previous to their widespread application under field conditions, research is needed to ensure the selection of the most suitable species. In this study, we inoculated two cyanobacterial species, Phormidium ambiguum (non N-fixing) and Scytonema javanicum (N-fixing), on different textured soils (from silt loam to sandy), and analyzed cyanobacteria biocrust development and evolution of physicochemical soil properties for three months under laboratory conditions. Cyanobacteria inoculation led to biocrust formation in all soil types. Scanning electron microscope (SEM) images showed contrasting structure of the biocrust induced by the two cyanobacteria. The one from P. ambiguum was characterized by thin filaments that enveloped soil particles and created a dense, entangled network, while the one from S. javanicum consisted of thicker filaments that grouped as bunches in between soil particles. Biocrust development, assessed by chlorophyll a content and crust spectral properties, was higher in S. javanicum-inoculated soils compared to P. ambiguum-inoculated soils. Either cyanobacteria inoculation did not increase soil hydrophobicity. S. javanicum promoted a higher increase in total organic C and total N content, while P. ambiguum was more effective in increasing total exopolysaccharide (EPS) content and soil penetration resistance. The effects of cyanobacteria inoculation also differed among soil types and the highest improvement in soil fertility compared to non-inoculated soils was found in sandy and silty soils, which originally had lowest fertility. On the whole, the improvement in soil fertility and stability supports the viability of using cyanobacteria to restore degraded arid soils.